Induction of Triticale (×Triticosecale Wittmack) In Vitro Androgenesis in Anther Cultures of F1 Hybrid Combinations, Varieties and Homogeneity Testing of Offspring Generation - József Kruppa; Osama Zuhair Kanbar; Kitti Andrea Tóth-Lencsés; Erzsébet Kiss; Lajos Bóna; Csaba Lantos; János Pauk (Life, 2023)
In cereal breeding, in vitro androgenesis methods are frequently applied to achieve doubled haploid (DH) plants. The aim of this study was to determine the effects of genotype (three registered varieties and eight F1 crossing combinations) and induction medium (W14mf and P4mf) on anther cultures (ACs) of triticale (×Triticosecale Wittmack). Androgenesis was induced in the treatment of each tested genotype, and the genotype significantly influenced the efficiency of AC, including in embryo-like structures (ELSs), albinos, green plantlets, and transplanted plantlets. The utilized medium also had a significant effect on the number of ELSs, albinos, and transplanted plantlets. Both media were suitable for AC in triticale DH plant production. The efficiency of AC was higher when using the P4mf medium (103.7 ELS/100 anthers, 19.7 green plantlets/100 anthers) than when using the W14mf medium (90.0 ELS/100 anthers, 17.0 green plantlets/100 anthers). However, the green plantlet regeneration efficiency of microspore-derived structures was 18.0% when using the W14mf medium, while this value was 15.9% in the case of ELSs induced with the P4mf medium. After nursery seed evaluation and propagation (DH1), the genetic homogeneity of the offspring generation (DH2) was tested using a molecular genetic method. Most of the tested DH lines showed homogeneity and were progressed into a breeding program after agronomic selection. Some DH lines showed inhomogeneity, which could be explained by the outcross inclination of triticale. We would like to call breeders’ attention to the outcross character of triticale and emphasize the vigilant propagation and maintenance of the triticale DH lines in breeding programs. Due to the outcross nature of triticale, even in self-pollinated genotypes, breeders should focus on careful maintenance, along with isolation in the case of line propagations, in triticale breeding programs.